COVID-19 Importation Risk From Olympic Athletes Prior to the Tokyo 2020 Olympics - Vico Lau, Hoi Yat; Xu, Mingda; Wang, Lin; Cowling, Benjamin J.; Du, Zhanwei (Frontiers in Physics, 2021)
The COVID-19 pandemic delayed the Tokyo 2020 Olympics for 1 year and sparked an unprecedented outbreak in Japan in early July 2021 due to the relaxation of social distancing measures for foreign arrivals. Approximately 11,000 athletes from 205 countries would gather at the Tokyo Olympics held from July 23 through August 8, 2021. Based on the prevalence of infection in different source locations and athlete numbers, we estimated that seven countries would introduce least one infection of COVID-19 to Tokyo and at most eleven unidentified infections after the three requested COVID-19 tests.